Assessment of chromium phytotoxicity, phytoremediation and tolerance potential of Sesbania sesban and Brachiaria mutica grown on chromite mine overburden dumps and garden soil. (August 2020) - Patra, Deepak Kumar; Pradhan, Chinmay; Kumar, Jagdish; Patra, Hemanta Kumar
Abstract: The addition of toxic chromium in agrarian soils from mine overburden dump is of serious concern. To combat the toxicity of chromium an experiment was carried out at the Department of Botany, Utkal University, India by taking the chromium rich overburden dump (OBD) from Sukinda chromite mine, India. Different proportions of chromium rich OBD (10%, 20%, 30%, 40%, 50%, 70% and 100% OBD) were supplied to garden soil and plants of legume and non-legume categories ( Sesbania sesban L. and Brachiaria mutica L.) were grown for assessment of phytoaccumulation ability of chromium, tolerance index, chlorophyll, protein and proline and the activity of oxidative inhibitors enzymes. After 60 days of experimentation, Cr phytotoxicity on physiological and biochemical parameters were assessed. The outcome of the results showed that the activity of antioxidant enzymes enhanced considerably in roots as compared to shoots with enhancing concentration of chromium. To compare the phytoaccumulation ability, the tolerance index (TI), bio-concentration factor (BCF) and transportation index (Ti) were measured in two different species. The results showed that at 100% OBD the TI, BCF and Ti of S. sesban have 22.30, 0.45 and 71.06 and B. mutica have 20.83, 0.43 and 42.45 respectively. The result showed that S. sesban not only had the highest bioaccumulation capacity of chromium but also have high tolerance index and transportation index as compared to B. mutica. Hence S. sesban can be recommended for phytostabilization programme to alleviate toxic chromium from chromite overburden mining sites. Graphical abstract: Relative distribution of Cr content in soils and plant parts after 60 days of growth with different soil amendements (T0 -T7 ). Image 1 Highlights: Two different plant species (Leguminous and Non-leguminous) in terms of ability to accumulate chromium from overburden dump of Sukinda chromite mine, India. Stress tolerance index (STI) and tolerance index (TI) were used to compare the endurance of the plants in chromium stress conditions. Bio-concentration factor (BCF) and transportation index (Ti) were applied to compare bioaccumulation ability. Based on BCF and Ti results, Sesbania sesban was chosen as a potential green tool for alleviation of chromium from contaminated sites.